International Comprehensive Ocean-Atmosphere Data Set (ICOADS) Release 2.5, Individual Observations ... - National Climatic Data Center/NESDIS/NOAA/U.S. Department Of Commerce; Ocean Climate Laboratory/National Oceanographic Data Center/NESDIS/NOAA/U.S. Department Of Commerce; Met Office/Ministry Of Defence/United Kingdom; Research Data Archive/Computational And Information Systems Laboratory/National Center For Atmospheric Research/University Corporation For Atmospheric Research; Pacific Marine Environmental Laboratory/OAR/NOAA/U.S. Department Of Commerce; Cooperative Institute For Research In Environmental Sciences/University Of Colorado; Deutscher Wetterdienst German Meteorological Service/Germany; World Meteorological Organization/United Nations; Integrated Science Data Management/Fisheries And Oceans/Canada; National Oceanography Centre/University Of Southampton; Center For Ocean-Atmospheric Prediction Studies/Florida State University; Physical Sciences Laboratory/Earth System Research Laboratory/OAR/NOAA/U.S. Department Of Commerce; et al. (UCAR/NCAR - Research Data Archive, 1984)
This dataset is superseded by ICOADS Release 3, Individual Observations [https://rda.ucar.edu/datasets/ds548.0/].The International Comprehensive Ocean-Atmosphere Data Set (ICOADS) is a global ocean marine meteorological and surface ocean dataset. It is formed by merging many national and international data sources that contain measurements and visual observations from ships (merchant, navy, research), moored and drifting buoys, coastal stations, and other marine platforms. Each report contains individual observations of meteorological and oceanographic variables, such as sea surface and air temperatures, wind, pressure, humidity, and cloudiness. The coverage is global and sampling density varies depending on date and geographic position relative to shipping routes and ocean observing systems.All three U.S. ICOADS partners (NOAA/ESRL, NOAA/NCDC, NCAR) offer various data access and format options. To review all available options see the ICOADS website [http://icoads.noaa.gov/products.html].IMPORTANT: The time ...